Factors associated with willingness to use oral pre-exposure prophylaxis (PrEP) in a fisher-folk community in peri-urban Kampala, Uganda - Bashir Ssuna; Anne Katahoire; Mari Armstrong-Hough; Dennis Kalibbala; Joan N. Kalyango; Flavia Matovu Kiweewa (BMC Public Health, 2022)
Abstract Background The World Health Organization (WHO) recommends the use of pre-exposure prophylaxis (PrEP) in key populations at elevated risk for exposure to HIV. If used effectively, PrEP can reduce annual HIV incidence to below 0.05%. However, PrEP is not acceptable among all communities that might benefit from it. There is, therefore, a need to understand perceptions of PrEP and factors associated with willingness to use PrEP among key populations at risk of HIV, such as members of communities with exceptionally high HIV prevalence. Objective To examine the perceptions and factors associated with willingness to use oral PrEP among members of fishing communities in Uganda, a key population at risk of HIV. Methods We conducted an explanatory sequential mixed-methods study at Ggaba fishing community from February to June 2019. Survey data were collected from a systematic random sample of 283 community members in which PrEP had not been rolled out yet by the time of we conducted the study. We carried out bivariate tests of association of willingness to use PrEP with demographic characteristics, HIV risk perception, HIV testing history. We estimated prevalence ratios for willingness to use PrEP. We used backward elimination to build a multivariable modified Poisson regression model to describe factors associated with willingness to use PrEP. We purposively selected 16 participants for focus group discussions to contextualize survey findings, analysing data inductively and identifying emergent themes related to perceptions of PrEP. Key results We enrolled 283 participants with a mean age of 31 ± 8 years. Most (80.9%) were male. The majority of participants had tested for HIV in their lifetime, but 64% had not tested in the past 6 months. Self-reported HIV prevalence was 6.4%. Most (80.6, 95%CI 75.5–85.0) were willing in principle to use PrEP. Willingness to use PrEP was associated with perceiving oneself to be at high risk of HIV (aPR 1.99, 95%CI 1.31–3.02, P = 0.001), having tested for HIV in the past 6-months (aPR 1.13, 95%CI 1.03–1.24, P = 0.007), and completion of tertiary education (aPR 1.97, 95%CI 1.39–2.81, P < 0.001). In focus group discussions, participants described pill burden, side-effects and drug safety as potential barriers to PrEP use. Conclusions and recommendations Oral PrEP was widely acceptable among members of fishing communities in peri-urban Kampala. Programs for scaling-up PrEP for fisherfolk should merge HIV testing services with sensitization about PrEP and also increase means of awareness of PrEP as an HIV preventive strategy .